Cardiac Rehabilitation Prevents Recurrent Revascularization in Patients With Coronary Heart Disease: A POPULATION-BASED COHORT STUDY IN TAIWAN. Issue 4 (July 2016) - Hou, Wen-Hsuan; Lai, Chien-Hung; Jeng, Chii; Hsu, Chuan-Chih; Shih, Chun-Ming; Tsai, Pei-Shan
Abstract : PURPOSE: To evaluate the effects of cardiac rehabilitation (CR) provided within the first 3 months of revascularization on reducing recurrent revascularization in patients with coronary heart disease in Taiwan. METHODS: In this population-based cohort study, we used the claims data of 1 million beneficiaries who were randomly selected from all beneficiaries enrolled in Taiwan's National Health Insurance program from 1996 to 2000. Between 2000 and 2007, 2838 patients underwent a first-event revascularization. Of these patients, 442 (15.6%) underwent CR within the first 3 months of admission for revascularization. The remaining 84.4% (n = 2396) served as the non-CR group. All the study patients were followed-up until the end of 2008 for any recurrent revascularization. A propensity score-adjusted Cox proportional hazard model was used to estimate the relative risk of recurrent revascularization associated with CR. RESULTS: During the 1- to 9-year follow-up, 69 patients (15.6%) in the CR group and 840 (35.1%) patients in the non-CR group experienced recurrent revascularization. The results of the propensity score-adjusted Cox proportional hazard regression analysis showed that CR was significantly associated with a reduced risk of recurrent revascularization with a hazard ratio of 0.48 (95% CI, 0.37 to −0.62). CONCLUSIONS: Cardiac rehabilitation within the first 3 months of revascularization is significantly associated with a reduced risk of recurrent revascularization. This preventive effect was more pronounced in men compared with other subgroups of patients. Abstract : This was a population-based cohort study on the associations between cardiac rehabilitation and the risk of recurrent revascularization in patients with coronary heart disease. Our results indicated that cardiac rehabilitation within the first 3 months of revascularization resulted in a significantly reduced risk of recurrent revascularization.